Protein variability in Malayan varieties of rice (Oryza sativa L.) - Quah, Soon Cheang (Faculty of Science, University of Malaya, 1972)

(untitled)
The protein contents of brown rice of fifty-nine varieties of rice cultivated in West Malaysia were found to lie in the range of 5.22 to 11.41 percent, with an overall mean of 8.41 percent. Protein contents of three popular Malayan varieties of rice, i.e. Bahagia, Mahsuri and Ria, grown at different locations in West Malaysia, varied considerably from location to location, but the variation in protein content was not large enough for the overall location effect to be statistically significant. Nitrogen fertilization at high dosage (70 lbs per acre and above) significantly increased the protein content of most of the varieties of rice studied. The varieties varied in their responses to nitrogen fertilization with respect to protein accumulation in the grains. Significant varietal(genotypic) differences were found with respect to protein content in the Malayan varieties of rice studied.